The Politics of Gender and Sexuality in Aristophanes' Lysistrata (Journal of the College of Basic Education, 2022)
Gender, sexuality and power have always shared a complex and dynamic relationship. As societal and cultural values shift, so too do the connections between these forces. This is especially well-demonstrated in Aristophanes’ Lysistrata, a Greek play originally performed around 411 BC. The age of the play belies the progressive nature of the text, a point documented in this paper, which uses the issues of gender and sexuality explored in the play to engage in a broader discussion on how sexuality and power relations between the sexes impact one another. The discussion is given background with a theoretical investigation of the various scholarly theories on gender, sexuality and power dynamics. Subsequently, the discussion focuses on the plot action and subtext of Lysistrata with an emphasis on how the female characters employed the power of sexual withholding in order to transpose traditional power structures. As the discussion will show, Aristophanes was neither feminist nor antiwar, but his progressive exploration of both lends great insight into the openness of socio-cultural discourse in ancient Greece